Beyond Scientific Facts: Climate Change Crisis in Earthquakes in London - Gülter, Isıl Şahin (My University, 2022)
“Ecodramaturgy” interrogates the extent to which the overall values in relation to nature and culture binary can be reconsidered and conveyed to the public through theatre and performance arts. Placing ecological reciprocity at the center of its dramatic and thematic content, ecodramaturgy places great hope in theatrical performances, which have the potential to alter mindsets of nature-culture interactions and transform au dience perceptions of ecological issues. These interactions have been remarkably evident in climate change theatre that emerges as the sub-genre of ecodramaturgy and employs climate change science on the stage. Drawing on the connection between climate change theatre and climate change science, this paper examines Mike Bartlett’s Earthquakes in London (2010), in which the playwright provides an opportunity for the audience to interact with the climate crisis beyond a scientific approach. In this regard, this paper indicates that climate change theatre, which appeals to the feelings through story and performance, can enable the audience to in teract with ecological thinking in unique ways and encourage them to take action against the climate change crisis.
Keywords: Çevre Çalışmaları; Felsefe; Sanat